Potential Essential Oils From Green Betel Leaf (Piper Betle L.) As A Natural Preservative For Meat Food - Elsa Dwi Ambarwati; Siti Nur Khafidhoh; Herlina Ayu Rachmanda; Naufal Khoirussyihab; Princes Orinta Oktavia; Endang Setyaningsih (Jurnal Impresi Indonesia, 2024)
Security food has become global attention, especially for a preservative experience to replace material chemistry. Oil essential oil leaf betel green (Piper betle L.) is a material experienced with eugenol, chavicol, and flavonoid content with characteristic antibacterial and antioxidant properties. Research This aims to study the effectiveness of oil essential oil leaf betel green as a preservative natural in meat products and determine the dose optimally. The experimental method uses a randomized block design (RBD) with four treatments: control and concentration of essential oil at 5 ml, 7.5 ml, and 10 ml. Observed parameters include pH, color, texture, and aroma of meat during seven-day storage, with data analysis using one-way ANOVA direction. Research results show that oil essential oil leaf betel green effectively maintains quality meat, with pH stability and better organoleptic parameters than the control. Oil essential oil at a concentration of 7.5 ml and 10 ml provides results best in slow down decay meat until seven day. Implications study This is development material preservative natural friendly? environmental and safe For industry food, at the same time reduce dependence on preservatives synthetic.